2007
DOI: 10.1002/app.25544
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray pole figures to assess orientation in PVC sheets

Abstract: A series of X-ray pole figures were obtained from oriented and unoriented rigid polyvinyl chloride sheets. From these, information about crystallite orientation in uniaxially and biaxially drawn sheets stretched at 908C was obtained. Uniaxial orientation produced two crystallite orientations with the extent of orientation increasing with draw ratio; for biaxial samples the chain direction (c) was distributed uniformly in the plane of the sheet, with the planar orientation improving as draw ratio increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the peak of the C-H stretching vibration at 2849 and 2919 cm À1 does not show differences between an unirradiated and irradiated WPVC/ZnB (M) significantly that the hydrocarbon backbone is not degraded by EB-irradiation. 15 16 Also, WPVC filled with zinc borate using the melting mixing method displays several peaks at 2 thetas 17.7, 18.0, 20.5, 21.7, 22.5, 23.7, 24.1, 25.8, 27.5, 28.6, 30.2, 30.5, 30.7, 32.8, 35.9, 36.6, and 42.9°r espectively, those characteristic spectra of 2 ZnO•3B 2 O 3 •3.5 H 2 O. 17 It was observed that peaks around 2 thetas 18.7 and 25.0 were less intense in comparison with those that represent the pristine WPVC because the addition of zinc borate decreases the crystalline phase on WPVC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the peak of the C-H stretching vibration at 2849 and 2919 cm À1 does not show differences between an unirradiated and irradiated WPVC/ZnB (M) significantly that the hydrocarbon backbone is not degraded by EB-irradiation. 15 16 Also, WPVC filled with zinc borate using the melting mixing method displays several peaks at 2 thetas 17.7, 18.0, 20.5, 21.7, 22.5, 23.7, 24.1, 25.8, 27.5, 28.6, 30.2, 30.5, 30.7, 32.8, 35.9, 36.6, and 42.9°r espectively, those characteristic spectra of 2 ZnO•3B 2 O 3 •3.5 H 2 O. 17 It was observed that peaks around 2 thetas 18.7 and 25.0 were less intense in comparison with those that represent the pristine WPVC because the addition of zinc borate decreases the crystalline phase on WPVC.…”
Section: Resultsmentioning
confidence: 99%
“…Figure1(d) illustrates the XRD diffraction pattern of WPVC and its composites with zinc borate salt fabricated by melt mixing and casting processes. XRD of WPVC shows diffraction broad peaks 2 theta around 17, 18.7, and 25 which are characteristic peaks of polyvinyl chloride sheet 16. Also, WPVC filled with zinc borate using the melting mixing method displays several peaks at 2 thetas 17.7, 18.0, 20.5, 21.7, 22.5, 23.7, 24.1, 25.8, 27.5, 28.6, 30.2, 30.5, 30.7, 32.8, 35.9, 36.6, and 42.9°r espectively, those characteristic spectra of 2 ZnO•3B 2 O 3 •3.5 H 2 O 17.…”
mentioning
confidence: 99%
“…The four films were examined in their initial state (i.e., 0%, 23°C) and at 50% strain for 23 versus 40°C as these conditions seemed to produce greater differences in gloss. The PUR film showed no crystallinity and the PVC film showed a weak peak at 2θ = 23.1 ° assigned to overlapping (210), (201), and (111) planes that was too small for analysis. This meant the XRD analysis was limited to the two PE/PP films.…”
Section: Resultsmentioning
confidence: 99%
“…Figure (10) illustrates the XRD diffraction pattern of WPVC and its composites with zinc borate salt fabricated by melt mixing and casting processes. XRD of WPVC shows diffraction broad peaks 2 theta around 17, 18.7, and 25 which are characteristic peaks of polyvinyl chloride sheet [17]. Also WPVC lled with zinc borate using the melting mixing method displays several peaks at 2 thetas 17.7, 18.0, 20.…”
Section: Xrd Of Fabricated Compositesmentioning
confidence: 98%